Alternative Approaches to High Energy Density Fusion. (March 2016) - Hammer, J
Abstract: This paper explores selected approaches to High Energy Density (HED) fusion, beginning with discussion of ignition requirements at the National Ignition Facility (NIF). The needed improvements to achieve ignition are closely tied to the ability to concentrate energy in the implosion, manifested in the stagnation pressure, Pstag . The energy that must be assembled in the imploded state to ignite varies roughly as Pstag -2, so among other requirements, there is a premium on reaching higher Pstag to achieve ignition with the available laser energy. The U.S. inertial confinement fusion program (ICF) is pursuing higher Pstag on NIF through improvements to capsule stability and symmetry. One can argue that recent experiments place an approximate upper bound on the ultimate ignition energy requirement. Scaling the implosions consistently in spatial, temporal and energy scales shows that implosions of the demonstrated quality ignite robustly at 9-15 times the current energy of NIF. While lasers are unlikely to reach that bounding energy, it appears that pulsed-power sources could plausibly do so, giving a range of paths forward for ICF depending on success in improving energy concentration. In this paper, I show the scaling arguments then discuss topics from my own involvement in HED fusion. The recent Viewfactor experiments at NIF have shed light on both the observed capsule drive deficit and errors in the detailed modelling of hohlraums. The latter could be important factors in the inability to achieve the needed symmetry and energy concentration. The paper then recounts earlier work in Fast Ignition and the uses of pulsed- power for HED and fusion applications. It concludes with a description of a method for improving pulsed-power driven hohlraums that could potentially provide a factor of 10 in energy at NIF-like drive conditions and reach the energy bound for indirect drive ICF.